Seismic Evidence for a Weakened Thick Crust at the Beaufort Sea Continental Margin. Issue 16 (29th August 2022) - Estève, C.; Liu, Y.; Koulakov, I.; Schaeffer, A. J.; Audet, P.
Abstract: The Canadian Beaufort Sea continental margin of northwestern Canada is a Cenozoic convergent margin, potentially representing a rare case of incipient subduction. Here, we produce P‐ and S‐wave seismic velocity models of the crust and the uppermost mantle using recordings from regional earthquakes. Our models reveal a northwest‐dipping very low‐velocity anomaly within the crust ( δV up to −15%) beneath the Romanzof Uplift. We interpret this low‐velocity feature to correspond to a weaker and thicker crust due to shortening and stacking of igneous and sedimentary rocks. The co‐location of the thickened crust and lack of present‐day seismicity indicates that north‐south compression is accommodated by slow, aseismic deformation in the narrow margin beneath the Romanzof Uplift or more broadly offshore. Neither interpretation requires nor precludes a subduction initiation process. Plain Language Summary: The Canadian Beaufort Sea continental margin (BSCM) of northwestern Canada may represent a unique location in the world where we observe a newly forming convergent margin, potentially representing a rare case of incipient subduction. We develop 3‐D seismic velocity models of the region from the crust to the uppermost mantle using regional earthquake recordings. The velocity models reveal a low‐velocity zone within the crust beneath the BSCM of the Yukon north slope. Seismic velocities in the crust predominantly depend on rock composition. Therefore, we suggest that variations in rock compositions influence the observed deformation processes and that crustal thickening occurs locally in the area. The observation of the thickened crust and lack of seismicity in the area suggest that deformation could be accommodated aseismically across the narrow margin or more broadly offshore. Neither interpretation requires a subduction initiation mechanism. Key Points: We present new seismic velocity models ( V P, V S and V P / V S ) of the Beaufort Sea continental margin (BSCM) We find localized thickened crust below the BSCM of northern Yukon Deformation is controlled by lateral variation in crustal strength attributed to different crustal compositions in the region